Quantifying patient effort in spontaneously breathing patient using negative component of dynamic Elastance. Issue 1 (July 2017) - Kim, Kyeong Tae; Redmond, Daniel P.; Morton, Sophie E.; Howe, Sarah L.; Chiew, Yeong Shiong; Chase, J. Geoffrey
Abstract: Respiratory mechanics of fully sedated patients can be easily estimated as the ventilator has full control of patient's work of breathing. However, in spontaneously breathing patients or patients whose work of breathing is only partially assisted, respiratory mechanics estimation is much more difficult. This difficulty is caused by un-modelled and variable patient effort introduced into the system. The Time-varying elastance model is a model that can estimate respiratory mechanics of spontaneously breathing patients with use of dynamic elastance. The model has a negative elastance component where measured airway pressure is decreasing, yet the air is flowing into the lungs due to patient effort. In this study, quantification of the negative elastance component is studied. Airway flow, pressure and Electrical Activity of Diaphragm signals from 22 invasively ventilated patients using Pressure Support mode are used for this analysis. Two methods have been used to quantify negative elastance, the zero-crossing method and trapezoidal method. The estimated median values of negative elastance using the zero-crossing method is: -3.289 [Interquartile range (IQR: -4.803 -2.504] cmH2 O/L and for trapezoidal method is: -1.899 [IQR: -2.362-1.664] cmH2 O/L. The correlation between electrical activity of the diaphragm and negative elastance is very weak as the R values across patients are: -0.0697 [IQR: -0.4972 -0.0255] for zero-crossing method and 0.0939 [IQR: -0.0293-0.3003] for trapezoidal method. Negative elastance is a conceptual component of the model and can be used to quantify patient demand. However, in this study, quantifying patient effort using negative elastance has little similarity to electrical activity of the diaphragm, as negative elastance appears to capture more than only patient effort. Further research is needed to use this metric to observe patient effort.